MORINGA: ALTERNATIVE FOR THE FOOD SECURITY, CLIMATE RESILIENCE AND LIVELIHOOD IMPROVEMENT IN NEPAL - Thakur, S. B.; Bajagain, A. (International Journal of Research -GRANTHAALAYAH, 2020)
Moringa oleifera L. is indigenous to northern foothills which includes Northern India, Pakistan and Nepal and genetic diversity is especially available in the Tarai region of Nepal including northern India. It's well climate stress adaptive nature, easy propagation, less input and intercultural operation requirement has proven to be boon in many ways. As it is the economical and reliable alternative for good nutrition, medicinal use, animal feed and fodder, plant supplement and soil reclamation, it can be touted as a miracle plant. Diverse form and edible utility of Moringa, helps for food and nutritional security for present and future. Likewise, carbon sinking attribute of its soft wood can be pivotal for curbing global warming and climate change. Moringa can thus help to create a well-nourished, healthy individual with happy family engaged in agriculture and agro-forestry blessed with good return and livelihood improvement. This review provides a brief overview about multipurpose use of Moringa and its implication to curb impacts on climate change, ensure food and nutrition security and sustain livelihood.